The Process of Making Investment Decisions for Teachers in the City of Tarakan - Malik, Aan Digita; Ahmad Juliana; Junaid, Muhammad Tharmizi; Oktavianti, Alma Dwi (International Journal of Management and Digital Business, 2023)
Low financial literacy and one's past behavior regarding finances that occurred among high school teachers in the city of Tarakan. The purpose of this study is the influence of past behavior variables, subjective norms, and financial literacy on investment decision making. In this study using descriptive quantitative methods that describe, explain, and describe a phenomenon. The technique used is through the distribution of questionnaires to respondents where in this study using primary data. The data analysis method used in the validity and reliability tests is using SEM, the normality test is using AMOS, the Autocorrelation test is using Durbin-Watson (DW test) through SPSS Software, the t test is using SPSS Software. The results showed that 1) past behavior and attitudes have a positive effect on investment decision making, 2) subjective norms have a positive effect on individuals to invest in the capital market, 3) financial literacy has a positive effect on decisions to invest in the capital market. The conclusions in this study are that 1) the better past behavior the better in deciding to, 2) the higher the subjective norm, the greater the desire to invest in the capital market, and 3) the higher the level of financial literacy carried out by an individual , it will be better in behaving and controlling his behavior to invest.